2016
DOI: 10.3961/jpmph.16.062
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Inquiry Into the Challenges of Medical Education for Retention of General Practitioners in Rural and Underserved Areas of Iran

Abstract: ObjectivesGeneral practitioners (GPs) retention in rural and underserved areas highly effects on accessibility of healthcare facilities across the country. Education seems to be a critical factor that affects GPs retention. Thus, the present study aimed at inquiry into medical education challenges that limit their retention in rural and underserved areas.MethodsA qualitative approach was applied for the aim of this study. Data were gathered via 28 semi-structured interviews with experts at different levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…The relation between demographic factors and retention in rural areas is hotly debated in the literature. Certain studies consider demographic factors as predictors of retention in rural areas (21,27), while others report that male physicians have a greater tendency to work in rural settings (22,28). However, our findings indicated that there were no gender differences when considering the tendency to stay in one's place of birth.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The relation between demographic factors and retention in rural areas is hotly debated in the literature. Certain studies consider demographic factors as predictors of retention in rural areas (21,27), while others report that male physicians have a greater tendency to work in rural settings (22,28). However, our findings indicated that there were no gender differences when considering the tendency to stay in one's place of birth.…”
Section: Discussioncontrasting
confidence: 80%
“…However, low retention rates in less developed rural areas are an important issue that some medical schools are trying to address. While some studies suggested reform in medical education could improve retention in rural areas (21)(22)(23), other factors such as development levels of service and demographic factors are critical, but are rarely addressed in studies (5).…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies in Iran have shown, the Iranian population does not trust general practitioners. [16]…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the passive health network, powerful private sector which have conflict of interest with UFPP, population freedom for choosing health provider, and different cultural norms are those factors that make UFPP more different from rural family physician program (4). Some studies conducted in different countries shows that diverse push factors within and outside health system might affect the tendency of human resources to join in the policies (13,14). Results of these studies are also different which clarifies the factors are multi-facetted and complex (14,15) and are mainly categorized into three groups including contextual/ environmental, personal and professional factors (13).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies conducted in different countries shows that diverse push factors within and outside health system might affect the tendency of human resources to join in the policies (13,14). Results of these studies are also different which clarifies the factors are multi-facetted and complex (14,15) and are mainly categorized into three groups including contextual/ environmental, personal and professional factors (13). In this regard the approach to the study might be different from one study to another study.…”
Section: Introductionmentioning
confidence: 99%